Evaluation of hard capsule application from seaweed: Gum Arabic-Kappa carrageenan biocomposite films - Fatmawati, Adam; Jurida, Jamaludin; Siti Hana, Abu Bakar; Ruwaida, Abdul Rasid; Zulkafli, Hassan (Taylor & Francis, 2020)
At present, plant-based hard capsule such as hydroxypropyl methylcellulose (HPMC) has a high demand in drug delivery application but the production process is expensive with limited reactant supply. κ-carrageenan has been used as a gelling agent in HPMC hard capsule production. This study aims to develop gum Arabic (GA)-κ- carrageenan biocomposite, a potential material to produce hard capsule. The GA-κ-carrageenan biocomposite films were prepared at different κ-carrageenan weight ratios of 33% (GC33), 50% (GC50) and 67% (GC67) at constant concentration of polyethylene glycol and alginate. The control films of GA film and κ-carrageenan film were compared. The film and hard capsule formed from GC67 shows the highest tensile strength and capsule loop of 36.21 MPa and 34.11 N, respectively at 1058 mPa.s solution viscosity at 300 rpm shear rate. The hard capsule disintegrated at 7.30 min. The addition of GA is compatible to make the hard capsule surface smoother. Thus, this biocomposite has the potential to be developed for future hard capsule.